ON DETERMINING THE D-STRUCTURE AND S-STRUCTURE OF WORLD LEADERS’ QUOTES - Ahsanu, Muhamad (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
This article projects the syntactical aspects of world leaders' quotes via the X-bar theory. Thereason why portraying the quotes utilizing the X-bar is due to the distinctiveness of the sentencepatterns of the quotes themselves. By distinctiveness, world leaders tend to use simplesentence pattern in their creating their quotes and due to this simplicity the quote has endlessimpact and becomes easily chanted and widely known. For instance, the quote 'I have adream' is very familiar to everyone's ears for partly it uses DP-VP-NP in the X-bar theory.This typicality is exposed through the primary research problems: what are the typical Dstructureconfigurations of the world leaders' quotes and how are the configurations transformedinto their S-structures? Thus, this article focuses on discovering the underlying representationsof the quotes of world leaders via the generative and transformational processes.The identified quotes are the internet-based data selected purposively. The article utilizes adescriptive and explanatory analysis.Keywords: D-structure, S-structure, world leaders’ quotes